PENDIDIKAN KEWARGANEGARAAN DALAM BUDAYA MULTIKULTURAL UNTUK MENANAMKAN SIKAP PATRIOTISME WARGA NEGARA - sulianti, ani (JPK (Jurnal Pancasila dan Kewarganegaraan), 2018)
Research aims to understand 1) the role of citizenship education, and 2). Multicultural culture in infuse values patriotism against a citizen.The research is the qualitative study, technique data collection by using the literature study and observation, technique the analysis used is a technique interactive data analysis consists of 4 stages, namely : 1 ) data collection, 2 ) reduction data, 3 ) the presentation of data, and 4 ) withdrawal of conclusion. The results of the study is as follows.1 ) citizenship education have a very crucial role in grow developed in mindset, the attitudes and behavior, unity peace, tolerant and values patriotism without leaving diversity who are already is typical of the indonesia. 2 ) of a culture multicultural owned indonesia very influential in infuse attitude patroitism where the cultural give a lesson valuable namely imparting flavor love towards a nation through a cultural compound owned by a nation.